Assessing the Temporal Organization of Walking Variability: A Systematic Review and Consensus Guidelines on Detrended Fluctuation Analysis - Ravi, Deepak K.; Marmelat, Vivien; Taylor, William R.; Newell, Karl M.; Stergiou, Nick; Singh, Navrag B. (Frontiers in Physiology, 2020)
Human physiological signals are inherently rhythmic and have a hallmark feature in that even distant intra-signal measurement are related to each other. This relationship is termed long-range correlation and has been recognized as an indicator of the optimal state of the observed physiological systems, among which the locomotor system. Loss of long-range correlations has been found as a result of aging as well as disease, which can be evaluated with detrended fluctuation analysis (DFA). Recently, DFA and the scaling exponent α has been employed for understanding the degeneration of temporal regulation of human walking biorhythms in e.g. Parkinson’s disease (PD). However, heterogeneous evidence on scaling exponent α values reported in the literature across different population groups has put into question what constitutes a healthy physiological pattern. Therefore, the purpose of this systematic review was to investigate the functional thresholds of scaling exponent α in young vs. older adults, as well as between patients with Parkinson’s disease and age-matched asymptomatic controls. Ageing and PD exhibited a negative effect size (i.e. led to decreased long-range correlations) of -0.20 and -0.53 respectively. Our meta-analysis based on 14 studies provides evidence that a mean scaling exponent α threshold of 0.86 (2 standard error [0.76; 0.96]) is able to optimally discriminate temporal organisation of stride interval between young and old, while 0.82 [0.72; 0.92] differentiates patients with Parkinson’s disease and age-matched asymptomatic controls. The optimal thresholds presented in this review together with the consensus guidelines for using DFA, might allow a more sensitive and reliable application of this metric for understanding human walking physiology that has been achieved to date.